A comparative study to evaluate the effects of two denture adhesives on Alveolar bone and Masticatory function - شهيد نور الدين; مجد سلمان (Latakia University Journal -Medical Sciences Series, 2023)
Objective: To compare the Denture Adhesives that contain zinc with those that do not contain zinc in terms of their effect on the Masticatory function using Sieving method and colorimetry method , and in terms of their effect on bone absorption. Materials & Methods: The study sample included 26 patients from patients with complete upper and lower dentures. For each patient, First x-ray was made immediately after making the dentures, and the Masticatory function tests were recorded using Sieving method and colorimetry method, and then second x ray were taken after a year to compare them with the control x ray for the investigation of radiological change.Results: The results of the statistical analysis showed that there were significant differences between the group of patients to whom zinc-containing adhesives were applied, compared to patients who were not given zinc-containing adhesives.Conclusion: Zinc-containing adhesives gave better clinical performance than non-zinc-containing adhesives, and this was reflected in the Masticatory function, stability of the devices, and finally bone absorption under the dentures. Keyword: Denture adhesives, Cream, Masticatory function, colorimetry method, Siveing method, bone resorption, Zinc.